Eficacia de la analgesia preventiva, con el uso de ketorolaco en el control del dolor postperatorio en pacientes sometidos a hernioplastia inguinal atendidos en el Hospital Manuel Ygnacio Monteros Valdivieso. - Ríos Sánchez, Katherine Laura (2016)
Introduction: Preventive analgesia with Ketorolac is an excellent alternative to guarantee postoperative pain relief. Objective: To compare the effectiveness of Ketorolac used in two analgesic modalities to control the DPO. Methodological design: A randomized clinical trial was conducted in a sample of 102 patients electively scheduled for hernioplasty inguinale with spinal anaesthesia In the Hospital "Manuel Y. Montero Valdivieso" of the province of Loja in the period from 1 April 2016 to 30 September 2016. Two groups were formed: A: they were given 60 mg of intravenous Ketorolac, immediately prior to the surgical incision. B: 60 mg of intravenous Ketorolac, prior to peritoneal closure. The quality of postoperative analgesia obtained in each group, the time of effective analgesia, the need for postoperative rescue analgesia and the perioperative adverse events. Results: Group A received a better quality of analgesia during the first postoperatively 3 hours. The time of effective analgesia was similar in both groups with an average duration between 6-7 hours. The requirements for rescue analgesics were minimal in both groups during the first 6 hours of the postoperative and increased considerably between 7 and 12 hours. No adverse effects were reported. Conclusions: The use of Ketorolac provides a better quality of postoperative analgesia when used in preincisional bolus. It offers a time of similar effective analgesia if it is used preincisional or before the peritoneal closure and reduces the requirements of rescue analgesia. Keywords: postoperative pain, Ketorolac